HUBUNGAN VERBAL PERSUASION, EMOSIONAL ARAUSAL (KECEMASAN) DAN MOTIVASI DENGAN EFIKASI DIRI IBU DALAM MEMBERIKAN IMUNISASI DPT 2 - ULVA NOVIANA (NHM PRESS, 2018)
DPT / DT immunization is an immunization action by giving DPT vaccine aims to provide immunity from germs diphtheria, pertussis, and tetanus. At BPM Suharijati Surabaya, Bulak Banteng Lor Bhineka Village on 9 December 2016 by giving questionnaires to 10 infant mothers aged 3-5 months. 7 out of 10 mothers answered questions in the questionnaire about hesitating to bring their infants to health for immunization. The objective of the study was to analyze factors related to the mother's self efficacy in providing immunization to health personnel. The design of this research is analytical with cross sectional approach. Independent variables are verbal persuasion, emotional arausal (anxiety), motivation and the dependent variable is self-efficacy of the mother in giving DPT immunization 2. Population of baby mother with amount of 30 people. Sample of 28 respondents with